2015
DOI: 10.1021/acs.cgd.5b00296
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4,6-Thiatriazinyl Radicals and Dimers: Structural and Electronic Tuning through Heteroaromatic Substituent Modification

Abstract: The functionalization of thiatriazinyl (TTA) radicals with pyridyl and thienyl moieties is described, and their influence at both the molecular and solid-state level has been investigated. Comparative electron paramagnetic resonance studies of 3,5-bis-(2-pyridyl)-1,2,4,6-thiatriazinyl (Py 2 TTA) and 3,5-bis-(2-thienyl)-1,2,4,6-thiatriazinyl (Th 2 TTA) reveal the impact of heteroaromatic substitution on the electronic structure, which is supported by density functional theory calculations. Single crystal X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…Based on single crystal X-ray analysis, Py 2 TTA • selfassociates in the solid state to form a sulphur-sulphur bridged co-facial dimer. 29 Such structural features have also been reported for other TTA derivatives. 35,36 Although dimerization occurs, stabilization of the radical may be accomplished through metal coordination, as has been shown to work with other radical based ligand systems.…”
Section: Synthesissupporting
confidence: 61%
See 2 more Smart Citations
“…Based on single crystal X-ray analysis, Py 2 TTA • selfassociates in the solid state to form a sulphur-sulphur bridged co-facial dimer. 29 Such structural features have also been reported for other TTA derivatives. 35,36 Although dimerization occurs, stabilization of the radical may be accomplished through metal coordination, as has been shown to work with other radical based ligand systems.…”
Section: Synthesissupporting
confidence: 61%
“…This challenge was overcome by changing the oxidant to N-chlorosuccinimide (NCS), affording Py 2 TTA • as a microcrystalline copper coloured solid (Scheme 1). 29 Purification can be accomplished by sublimation under vacuum or recrystallization in hot acetonitrile (MeCN). Based on single crystal X-ray analysis, Py 2 TTA • selfassociates in the solid state to form a sulphur-sulphur bridged co-facial dimer.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The intermolecular distance of the S–S contact in the π-dimer was estimated to be 2.98 Å, which is significantly shorter than the sum of the van der Waals radii. 16,17 The crystal packing structure revealed that no significant dimer–dimer interactions were present in any of the axis projections (Figures 3a and S9). Powder XRD measurements (Figures 3b, S10, and S11) revealed that the sharp diffraction peaks in the DM-GC state nearly disappeared in the PM-OL state, changed to a distinctly sharp pattern in the PM-OS state, and finally returned back to the original crystal pattern in the DM-GS state.…”
Section: Resultsmentioning
confidence: 99%
“…6 Since Py 2 TTA can exist as a neutral radical in solution, the generation of the oxide may be attributed to the generation of the radical, which is known to be susceptible to oxidation. 8 Alternatively, the generation of the oxide may occur following coordination to the metal ion, which pulls electron density of the anionic charge towards the metal centre leaving the sulphur atom of the TTA ring susceptible to oxidation. In order to elucidate the reaction process, time dependent 1 H NMR studies were carried out on the in situ reaction between Y(NO 3 ) 3 Á6H 2 O (2 equiv.)…”
mentioning
confidence: 99%